Crisis and Consumption in Europe - Secondulfo, Domenico; Setiffi, Francesca (Italian Sociological Review, 2016)
The crisis has been gnawing away at Europe for years now. The various European states, each with their own particular economic, cultural and social characteristics, have responded differently to the challenge, often with reactions that have brought those very differences that distinguish them to the fore. Within the general landscape of these increasing social and economic differences, both between the states and within them - also brought about by the deep crisis suffered by the same middle-class which led the economic and social expansion that came before - it is possible to observe some significant differences in both the reactions and consequences across the various member states. The problem has been approached from many perspectives in economic, politological and sociological scholarship, but here we have chosen to examine it through the consumer. The special section “Crisis and Consumption in Europe” represents an attempt to understand the different strategies of reaction adopted by European consumers following the economic and social changes that began in 2008.